The frequencies of amino acids in secondary structural elements of globular proteins - NACAR, CEVDET (My University, 2023)
Objective: The frequencies of amino acids in proteins for different structural levels have been determined by many studies. However, due to the different content of data sets, findings from these studies are inconsistent for some amino acids. This study aims to eliminate the contradictions in the findings of the studies by determining the frequencies of the amino acids in all structural level of globular proteins. Methods: The frequencies of the amino acids in overall protein, in secondary structural elements (helix, sheet, coil) and in subtypes of secondary structural elements (α-, π-, and 310-helices, and first, parallel and anti-parallel strands) were calculated separately using a data set including 4.882 dissimilar globular peptides. The frequencies of the amino acids were calculated as the ratio of the total number of a specific residue in related structure to the total number of all residues in the related structure. Results: The frequencies of residues determined in this study is partially in consistent with the other studies. The differences are probably due to the data set contents of the studies. The frequencies of the amino acids in subtypes of secondary structural elements were determined for the first time in this study. Conclusions: Variations in the frequencies of PRO residue in 310-helix structure and of ILE, LEU, and VAL residues in strands of sheet structure are valuable findings for the improvement of secondary structure prediction methods, as they can be used as secondary structural elements markers.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyofizik; Medicine; Health Sciences; Fundamental Medical Sciences; Biophysics; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Biyoloji ve Biyokimya; TIP, GENEL & DAHİLİ; BİYOFİZİK; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; BIOLOGY & BIOCHEMISTRY; MEDICINE, GENERAL & INTERNAL; BIOPHYSICS; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Yaşam Bilimleri; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Life Sciences; amino acid; globular protein; secondary structure